Severe Falciparum Malaria with Multiple Complications in Sanglah Hospital Denpasar - Evelin Vianetha Prima Snak; I Nyoman Wande; Ni Nyoman Mahartini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Malaria is caused by Plasmodium, which is transmitted through the bite of infected female Anopheles mosquitoes. Plasmodium falciparum causes the most severe form of malaria and can be life-threatening. A 63-year-old male with decreased consciousness, fever, chills, vomiting, and joint pain. The patient works in the Ivory Coast, malaria-endemic areas. Physical examination found clouding of consciousness and jaundice. Laboratory examination results are leukocytosis with eosinophilia and thrombocytopenia, increased of Aspartate Aminotransferase (AST), Alanine Aminotransferase (ALT), total bilirubin, direct and indirect bilirubin, Blood Urea Nitrogen (BUN), creatinine, decreased of estimated Glomerular Filtration Rate (e-GFR), decreased random plasma glucose. Urinalysis showed macroscopic hematuria, positive blood, and protein are found, and erythrocyte sediment is increased. A blood gas analysis examination revealed metabolic acidosis. Rapid Diagnostic Test (RDT) showed positive for Plasmodium falciparum. The blood smear showed leukocytosis with eosinophilia and thrombocytopenia and the ring-form trophozoites stage of Plasmodium falciparum. The definitive diagnosis of falciparum malaria is confirmed by microscopic peripheral blood smear and malaria RDT for antigen detection. An overall investigation concluded the patient diagnosed is severe falciparum malaria with various complications including hypoglycemia, jaundice, and acute kidney failure. The patient died on the first day after being treated in Sanglah Hospital, Denpasar.